Literature Study: The Effect of The Problem-Based Learning Model Assisted by The Flipped Classroom on Mathematical Creative Thinking Ability - Dewi Mariani; Mustaji Mustaji; Utari Dewi (Publikasi Indonesia, 2025)
The development of mathematical creative thinking abilities is a crucial goal in modern education, as these skills enable students to approach complex problems innovatively and adapt to diverse challenges. However, traditional teaching methods often fail to nurture creativity, focusing instead on rote learning and procedural tasks. This study aims to investigate the impact of integrating the Problem-Based Learning (PBL) model and the Flipped Classroom approach on enhancing students' mathematical creative thinking abilities. The research employs a Systematic Literature Review (SLR) methodology, analyzing previous studies that explore the effects of these pedagogical strategies individually and in combination. Data were collected and synthesized through a rigorous process of identification, screening, and inclusion based on predefined criteria. The findings reveal that the integration of PBL and the Flipped Classroom significantly improves students' flexibility, originality, and ability to generate innovative solutions in mathematics. PBL fosters collaborative problem-solving and real-world application, while the Flipped Classroom prepares students with foundational knowledge, allowing class time to focus on exploration and creativity. This research highlights the potential of innovative teaching models to transform mathematics education by creating dynamic and student-centered learning environments. The results provide valuable insights for educators seeking to foster higher-order thinking skills and creativity in their students.